Dual-Vector Lower Trapezius Tendon Transfer With Quadriceps Tendon Allograft in Massive Rotator Cuff Tear: STAR (Superior Trapezius Anatomic Reconstruction) Procedure - Carlos Vicente Andreoli, Ph.D.; Paulo Henrique Schmidt Lara, Ph.D.; Leandro Masini Ribeiro, M.D.; Franciele Silva Bernardo, M.D.; Paulo Santoro Belangero, Ph.D.; Alberto de Castro Pochini, Ph.D.; Benno Ejnisman, Ph.D. (Arthroscopy Techniques)
In the context of massive rotator cuff tear, attempted repair—partial/complete—remains the standard of care. However, outcomes vary, and retear rates are high. The lower trapezius tendon transfer for posterosuperior irreparable rotator cuff tears provides active external rotation and shoulder abduction. Superior capsule reconstruction is another option for enhancing range of motion and pain relief in severe cuff tears. Combining superior capsule reconstruction and lower trapezius tendon may offer improved motion and strength for irreparable posterosuperior rotator cuff tears. This Technical Note aims to describe a reproducible technique for combining both procedures in one surgery, using the same allograft tendon for both. The use of quadriceps tendon allograft offers the potential for combined lower trapezius transfer and superior capsule reconstruction, providing a viable option for irreparable posterosuperior rotator cuff tears.